PREVALENCE OF STAPHYLOCOCCUS AUREUS AND ESCHERICHIA COLI ON LEAFY VEGETABLES SOLD AT A COMMUNITY MARKET - CELESTINA C UGWU (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The aim of this study is to evaluate the presence of Staphylococcus aureus and Escherichia coli in leafy vegetables sold at a community market as well as determine their antibiotic susceptibility patterns on some commonly used antibiotics. Methods: A total of thirty (30) different leafy vegetables of different species were bought from different vendors at Eke-Agbani market in Nkanu West L.G.A. The bacteria were isolated and identified using standard microbiological methods. Antibiotic susceptibility patterns were determined using the disk diffusion method. Results: The mean bacterial load of S. aureus and E. coli from these samples ranged from 4.2×106 to 8.3×106 cfu/g and 4.7×106 to 7.6×106 cfu/g, respectively. The number of positive samples and negative samples are 18 (60%) and 12 (40%), respectively. The percentage distribution of both S. aureus and E. coli was 50%, respectively. The susceptibility of the isolates to antibiotics showed that all E. coli isolates had 100% sensitivity to ciprofloxacin, tarivid, reflacin, ceporex, and augmentin. All the S. aureus isolates had 100% sensitivity to gentamycin, amoxicillin, and ciprofloxacin. All the S. aureus isolates had 100% resistant to chloramphenicol. Conclusions: The results revealed the presence of S. aureus and E. coli in the vegetables screened. The presence of these bacteria may pose a serious threat to human health as some of these vegetables are consumed without proper cooking. Therefore, adequate measures should be taken by consumers to ensure proper washing before consuming as well as advising the public on antibiotic use.